The tetrastichine wasps (Hymenoptera: Chalcidoidea: Eulophidae) associated with galls on Erythrina species (Fabaceae) in South Africa, with the description of five new species - Prinsloo, Gerhard L.; Kelly, Janine A. (Zootaxa, 2009)
Five new tetrastichine eulophid species are described from both sexes from South Africa: Quadrastichus ingens, Q. gallicola and Q. bardus induce leaf, petiole and shoot galls on indigenous Erythrina species (Fabaceae); Aprostocetus nitens and A. tritus are parasitoids of the Quadrastichus species; Q. bardus and A. nitens are also recorded from Tanzania and comments are provided on A. exertus La Salle, known from Tanzania and South Africa as a parasitoid of Q. erythrinae Kim and Q. ingens. A key is provided for the separation of the six eulophid species now known from South Africa.